Γ-Oryzanol alleviates acetaminophen-induced liver injury: roles of modulating AMPK/GSK3β/Nrf2 and NF-κB signaling pathways. Issue 10 (4th October 2019) - Shu, Guangwen; Qiu, Yunhan; Hao, Ji; Fu, Qian; Deng, Xukun
Abstract : γ-Oryzanol alleviates acetaminophen-induced liver injury in mice. Abstract : Acetaminophen (APAP) overdose is a major cause of drug-induced liver injury worldwide. Our current study was performed to assess the potential protective effects of γ-oryzanol (ORY) on APAP-induced liver injury in mice and explore the underlying molecular mechanisms. We unveiled that ORY alleviated the APAP-induced death of HL-7702 hepatocytes in vitro and liver injury in mice. Moreover, ORY promoted the nuclear translocation of Nrf2, increased the expressions of Nrf2-downstream antioxidative enzymes, including HO-1, NQO1, GCLC, and GCLM, and thereby restrained APAP-induced oxidative stress in hepatocytes. Moreover, ORY modulated the AMPK/GSK3β axis that acts upstream of Nrf2 in hepatocytes. Compound C, an inhibitor of AMPK, prevented the ORY-mediated activation of Nrf2 and protection against APAP toxicity in HL-7702 hepatocytes. Additionally, in the liver of mice receiving APAP, ORY suppressed the nuclear translocation of the NF-κB p65 subunit, downregulated the expressions of iNOS and COX-2, and reduced the levels of pro-inflammatory factors including TNF-α, IL-1β, IL-6, and NO. Taken together, our findings revealed that ORY is capable of ameliorating APAP-induced liver injury. The modulation of AMPK/GSK3β/Nrf2 and NF-κB signaling pathways is implicated in the hepatoprotective activity of ORY.